Aplikasi Arisan Marga Berbasis Web Menggunakan Metode Linear Congruential Generator - Yanto, Rudi; Meiyanti, Ruci (Fakultas Ilmu Komputer, 2023)
The advancement of technology has significantly impacted various aspects of life, including the traditional practice of